Millstone making in Scotland - Tucker, D Gordon (Proceedings of the Society of Antiquaries of Scotland, 1985)
Identifies two main 18th-19th century types, based on urban and rural manufacture respectively. Imported French burrs and local rock (special importance of Kain Hill quarry). Known manufacturers listed.